Functional morphotypes as proxies for large-scale assessment of marine nematode assemblages along the Indian coastline - Sanofar Khokher; Joydeep Dutta; Elisa Baldrighi; Amita Choudhury; Abhilash K. R.; Deepak Samuel (Regional Studies in Marine Science, 2026)

Electrifying Sagar Island, West Bengal, India: advancing multiple SDGs through integrated coastal policy and sustainable development - Satyendra Kumar; Selvin Pitchaikani J; Deepak Samuel V; Ramesh R (Journal of Coastal Conservation, 2026)

Scaling the Spatial and Temporal Effects of Wrack Disturbance Across a Saltmarsh Landscape - Matt J. Pierce; Tyler Lynn; Julie Grissett; Shelby Ziegler; Sydney Williams; Satyatejas Reddy; Samuel Dong; Cailyn Bowser; Merryl Alber; Steven C. Pennings; Deepak R. Mishra; Amanda C. Spivak; et al. (Estuaries and Coasts, 2026)
Disturbance effects are rarely distributed uniformly over space or time. Thus, scaling up the effects of disturbances requires detailed measurements across multiple spatial scales. To characterize disturbance from wrack we used monthly images from an unmanned aerial vehicle (UAV) in a 144,500 m 2 Spartina alterniflora saltmarsh on Sapelo Island, Georgia (USA), from March 2020 to December 2022. Prior work as well as the results of our study demonstrated that wrack persisting for ≥ 2 months (“persistent wrack”) affects underlying vegetation. During our study, persistent wrack comprised ~ 30% of the average monthly wrack area (161 m 2 or ~ 0.10% of the total S. alterniflora marsh) and showed an annual peak between July and September. We quantified the effects of persistent wrack on live S. alterniflora , two invertebrate taxa (snails and burrowing marsh crabs), and porewater via field surveys of paired wrack-affected and wrack-free controls. At each monthly sampling point relative to controls, S. alterniflora stem density in wrack-affected plots was 41% lower on average and snail density lower by 25%, while crab burrow abundance and porewater parameters remained similar between controls and disturbed plots. Using wrack area from monthly UAV imaging, we scaled-up plot-level effects to marsh-level and found a < 1% change per species in abundance. Thus, our data suggest that even if wrack has strong local effects, the effects can be minor in S. alterniflora marshes at a landscape scale. This study demonstrates that field monitoring to quantify the effects of disturbances, coupled with repeat UAV imagery, allows for scaling that better contextualizes the overall impact than either method alone.

Development of multivariate health index for tropical seagrass meadows: a case study from Pulicat Lagoon, India - C. Viswanathan; J. Joyson Joe Jeevamani; K. Balachandar; K. Arumugam; K. Paramasivam; Dipnarayan Ganguly; R. Muruganandam; V. Deepak Samuel; R. Purvaja (Environmental Monitoring and Assessment, 2026)

Decolonising hydrology: Reflecting on positionalities for sustainable and just futures - Kwok P. Chun; Thanti Octavianti; Lori Bradford; Mark Reeves; Mohsen Nagheeby; Adeyemi Olusola; Ben C. Howard; Natalie Ceperley; Giulio Castelli; Albert Nkwasa; Yus Budiyono; Graham Strickert; et al. (Environmental Science & Policy, 2026)

Managing the recovering saltwater crocodile population in a marine protected area with human-wildlife conflict: A population viability analysis approach - V. Deepak Samuel; J. Joyson Joe Jeevamani; Yusuke Fukuda; R. Muruganandam; Meeta Biswal; R. Ramesh; R. Purvaja (Journal for Nature Conservation, 2025)

Functional Diversity of Seagrass-associated Macrofaunal Assemblages in a Brackishwater Lagoon of India: A multi-trait Approach - K. Paramasivam; K.R. Abhilash; C. Praveen Raj; C. Viswanathan; R. Sankar; J. Joyson Joe Jeevamani; Darwin Ramteke; V. Deepak Samuel; R. Purvaja (Thalassas: An International Journal of Marine Sciences, 2025)

Assessment of beach morphological characteristics and conservation strategies for blue flag beaches on the West Coast of India - J. Selvin Pitchaikani; Subbareddy Bonthu; R. Muruganandam; C. Viswanathan; K. K. Manodheepan; V. Deepak Samuel; Purvaja Ramachandran; R. Ramesh (Journal of Coastal Conservation, 2024)

Microplastics in oral healthcare products (OHPs) and their environmental health risks and mitigation measures - G.B Protyusha; Kavitha B; R.S Robin; Nithin A; T.R Ineyathendral; S. Shruthi Shivani; Anandavelu I; Shyam Sivasamy; V. Deepak Samuel; Purvaja R (Environmental Pollution, 2024)

Assessment of benthic habitats of highly threatened oyster reefs of Pulicat Lake, India - Darwin Ramteke; K. Paramasivam; C. Viswanathan; K.R. Abhilash; J. Joyson Joe Jeevamani; V. Deepak Samuel; R. Sankar; R. Muruganandam; R. Purvaja; R. Ramesh (Regional Studies in Marine Science, 2023)

Fermentative valorisation of xylose-rich hemicellulosic hydrolysates from agricultural waste residues for lactic acid production under non-sterile conditions - Rylan Cox; Vivek Narisetty; Eulogio Castro; Deepti Agrawal; Samuel Jacob; Gopalakrishnan Kumar; Deepak Kumar; Vinod Kumar (Waste Management, 2023)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Benthic foraminifera as an environmental proxy for pollutants along the coast of Chennai, India - K. Balachandar; C. Viswanathan; R.S. Robin; K.R. Abhilash; R. Sankar; V. Deepak Samuel; R. Purvaja; R. Ramesh (Chemosphere, 2023)

First Record of Galatheid Squat Lobster, Shinkaia crosnieri Baba & Williams, 1998 (Decapoda: Galatheoidea) From Cold-seep Environment of the Indian Ocean - Maria-Judith Gonsalves; Shivam Tiwari; Vinay P. Padate; Jignesh N. Trivedi; V. Deepak Samuel; C. Viswanathan (Thalassas: An International Journal of Marine Sciences, 2022)

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

Increasing signs of degradation of shallow water coral reefs due to repeated bleaching and spatial competition among benthic substrates - Bitopan Malakar; S. Venu; V. Deepak Samuel; K. R. Abhilash (Wetlands Ecology and Management, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

An integrated approach to assess coastal vulnerability versus fisheries livelihood sustainability: Strategies for climate change adaptation in Sindhudurg, west coast of India - J. Joyson Joe Jeevamani; P. Priya; J. Amali Infantina; K. R. Abhilash; Durga Prasad Behera; V. Deepak Samuel; R. Soundararajan; R. Purvaja; R. Ramesh (Environment, Development and Sustainability, 2021)

New Distributional Record of Petal-Eyed Swimmer Crab, Vojmirophthalmus minabensis (Sakai 1961) (Portunidae: Podophthalminae) from Indian Waters - Mariasingarayan Yosuva; Chinnathambi Viswanathan; Vijay Kumar Deepak Samuel; Kanagaraj Chamundeeswari; Ramachandran Purvaja; Ramachandran Ramesh (Thalassas: An International Journal of Marine Sciences, 2020)

Sustainability at a cost: An inceptive analysis of “extended” fishing ban on the livelihoods of fishers of Tamil Nadu - John Amali Infantina; Parasuram Priya; Vijay Kumar Deepak Samuel; Kottarathil Rajendiran Abhilash; Ramchandran Purvaja; Ramachandran Ramesh (Fisheries Management and Ecology, 2020)
An emphasis on sustainable marine fish production has paved the way for the enactment of Marine Fisheries Regulation Acts and subsequent regulations in India. A closed season ban on fishing has been one of the very few successful regulatory measures since its introduction in 2001 in Tamil Nadu. Since 2017, the fishing ban period has been extended from 45 to 60 days for the east coast of India, for ecosystem‐based marine fisheries management. This study analyses the socioeconomic impacts of change in the fishing ban (closed season) across the four coastal zones of Tamil Nadu. For the past 10 years, CPUE has been stable or increased marginally. Among the four coasts, the relative change in employment and labour income loss was highest for Palk Bay (36.84%). Transaction costs of implementation of the ban caused an additional expense of Rs 496.5 million to the Government in 2017 and the overall total labour income loss has leaped from Rs 1,638.2 to 2,100.2 million due to the extension of the ban. The fishing ban has aided in the recovery of habitat and regeneration of stock through recruitment. Training and capacity building on alternative livelihood options are highly recommended to enable the workers to cope with the ban period.

Impact of long-term seaweed farming on water quality: a case study from Palk Bay, India - K. R. Abhilash; R. Sankar; R. Purvaja; Samuel V. Deepak; C. R. Sreeraj; P. Krishnan; V. Sekar; Amit K. Biswas; G. Kumarapandiyan; R. Ramesh (Journal of Coastal Conservation, 2019)

Assessment of biochemical components and enzyme activities in the estuarine crab Scylla tranquebarica from naphthalene contaminated habitants - K. Vijayavel; C. Anbuselvam; M. P. Balasubramanian; V. Deepak Samuel; S. Gopalakrishnan (Ecotoxicology, 2006)